Basic guide to medical emergencies in the dental practice - Jevon, Philip; Strickland, Celia; Meese, Tessa; Pooni, J. S. (Jagtar Singh) (Chichester Wiley-Blackwell, 2014)
'The'Basic Guide to Medical Emergencies in the Dental Practice' is a must have book for all dental care professionals and general dentists. Written in a clear and accessible style, chapters cover such key topics as patient assessment, adult resuscitation, respiratory and cardiac disorders, paediatric emergencies, emergency equipment and law and ethics. The 2nd edition has been fully revised and updated in line with the Resuscitation Council's Guidelines and now includes a brand new chapter on the'Principles of First Aid''--Provided by publisher.
Contents note continued: Oral glucose solution/tablets/gel/powder -- Salbutamol inhaler -- Conclusion -- References -- 14.Principles of first aid in the dental practice -- Introduction -- Priorities of first aid -- Responsibilities when providing first aid -- Assessment of the casualty -- Wounds and bleeding -- Minor burns and scalds -- Poisoning, stings and bites -- Importance of record keeping -- Summary -- References -- 15.Professional, ethical and legal issues -- Introduction -- The scope of a dental professional's accountability -- The fifth sphere of accountability -- Legal requirements for consent and acting in a patient's best interests -- Duty of confidence owed to patients by dental professionals.
Previous edition: 2010.
Includes bibliographical references and index.
Keywords: Dental Care -- methods; Emergency Treatment -- methods; Emergencies